Intestinal type adenocarcinoma of the endometrium with signet ring cells, a rare aggressive variant - Kieran Seay; Bethany Bustamante; Alexander Truskinovsky; Andrew Menzin; Gary L. Goldberg (Elsevier, 2022)
Objective: Intestinal type mucinous adenocarcinoma (iMACE) is a rare and unusual variant of mucinous carcinoma of the endometrium that can show focal features of poorly differentiated adenocarcinomas of gastric, pancreatic or intestinal origin by producing signet ring cells. To date, only two reported cases of signet ring cells as a morphological feature of iMACE have been reported. Alterations in E-cadherin expression have been linked to increased metastatic potential, tumor dedifferentiation, and deep myometrial invasion in endometrial carcinomas. The presence or absence of E-cadherin in iMACE with signet-ring cells has not been studied. Thus, we sought to analyze E-cadherin expression in this aggressive variant of endometrial carcinoma. Cases: Diagnosis of iMACE with signet ring cells was rendered with the aid of immunohistochemical staining and histological analysis. Average age of diagnosis was 72 with the presenting complaint of postmenopausal bleeding in all three women. Focal loss or weakly positive E-cadherin expression was seen in areas of signet-rings cell morphology in all three cases. Conclusion: This case report adds to the body of literature that demonstrates the aggressive nature of intestinal differentiation in the endometrium. In addition, this report suggests that the presence of signet-rings cells and loss of E-cadherin expression may render a poorer prognosis as seen in other parts of the body.